Normal values of proximal aorta diameters in healthy Sub Saharan Africans: The TAHES study. Issue 4 (8th March 2022) - Vandroux, David; Aboyans, Victor; Houehanou, Yessito Corine; Saka, Dominique; Sonou, Arnaud; Houinato, Dismand; Preux, Pierre Marie; Magne, Julien; Lacroix, Philippe; ,
Abstract: Objectives: Reported ranges of normal values are mostly issued from studies performed with Caucasians. This study is a part of TAHES, a population‐based prospective cohort study in Benin and aims to establish normal reference values for echocardiographic diameters of the proximal aorta in Africans. Methods: Transthoracic echocardiography (TTE) examinations were performed by four cardiologists following pre‐defined protocols, and analyzed off‐line by a single observer. Aortic root diameters were measured during diastole for sinuses of Vasalva (SV), sinotubular junction (STJ) and proximal ascending aorta (AA), and during systole for annulus. Upper limits were defined as the 95th percentiles. Results: We included 513 normotensive, non‐diabetic, and cardiovascular disease‐free individuals (206 men, 307 women, age 40 ± 14 years). The diameters of the proximal aorta were significantly greater in men. The inner‐edge‐to‐inner‐edge non‐indexed upper values for the annulus, SV, STJ and AA were respectively 25, 34, 28.5, 32 mm in men and 22, 30, 26, 30 mm in women. The leading‐edge‐to‐leading‐edge upper values were respectively 38, 35, 36 for men and 34, 33, 32 mm for women. No significant differences between sexes were recorded for body surface area (BSA)‐indexed diameters of the annulus, STJ and AA. BSA‐indexed SV dimension was greater in men than women were. SV, STJ, AA indexed‐diameters correlated with age in both sexes but not for annulus indexed‐diameter. Conclusion: Normal values from a general population in West Africa could to differ from those established in Caucasian populations. Ethnic‐specific reference diameters are here proposed for appropriate diagnosis of proximal aortic diseases in sub‐Saharan Africa.